Money Laundering through Cryptocurrency and Its Arrangements in Money Laundering Act - Andhira Wardani; Mahrus Ali; Jaco Barkhuizen (Lex Publica, 2022)
The development of the modus operandi of money laundering become a major concern. Cryptocurrency technology has the potential to become a new media for money laundering because law enforcement officials still use to this technology, this technology which has a pseudonymous and even anonymous character is a new means for money laundering perpetrators to disguise their crimes. This study aims to examine how cryptocurrency is used as the modus operandi of money laundering and how is the readiness of regulations in Indonesia, especially Law No. 8 of 2010 in prosecuting money laundering offenders with the cryptocurrency modus operandi. This study uses a normative juridical method with legal materials from literature studies and uses a statutory regulation approach. The results of this study are the use of crypto as a mode of money laundering due to peer-to-peer networks, namely the absence of third parties to supervise crypto transactions, high user privacy, and transaction flexibility. Abstrak. Berkembangnya modus operandi pencucian uang menjadi perhatian utama. Teknologi cryptocurrency berpotensi menjadi media baru TPPU dikarenakan masih awamnya teknologi tersebut oleh aparat penegak hukum, teknologi yang memiliki karakter pseudonymous bahkan anonymous ini menjadi sarana baru bagi pelaku TPPU untuk menyamarkan kejahatannya. Penelitian ini bertujuan untuk mengkaji bagaimana pemanfaatan cryptocurrency sebagai modus operandi TPPU dan bagaimana kesiapan regulasi di Indonesia khususnya Undang-Undang Nomor 8 Tahun 2010 dalam menjerat pelaku TPPU dengan modus operandi cryptocurrency. Penelitian ini menggunakan metode yuridis normatif dengan bahan hukum studi kepustakaan dan menggunakan pendekatan peraturan perundang-undangan. Hasil penelitian ini adalah pemanfaatan kripto sebagai modus pencucian uang dikarenakan jaringan peer-to-peer yaitu tidak adanya pihak ketiga yang melakukan pengawasan transaksi kripto, privasi pengguna yang tinggi, dan fleksibilitas transaksi. Kata kunci: Modus Operandi, Cryptocurrency, Pencucian Uang, Indonesia